1998
DOI: 10.1016/s0960-9822(07)00477-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein regulation: Tag wrestling with relatives of ubiquitin

Abstract: Ubiquitin modification is a well established way of regulating protein levels and activities. Modification by related ubiquitin-like proteins is turning out to have a diverse range of interesting cellular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…The concentrations of these transcriptional regulators are controlled, at least in part, through proteasome-mediated protein degradation. The first step in this process, the ubiquitination of proteins, which are subsequently degraded by the 26 S proteasome complex, is a highly regulated process leading to the modulation of transcription factor activity (13). In this report, it is shown that the ubiquitin-proteasome pathway controls the degradation of PPAR␣ protein and as such modulates the concentration of PPAR␣ in hepatocytes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The concentrations of these transcriptional regulators are controlled, at least in part, through proteasome-mediated protein degradation. The first step in this process, the ubiquitination of proteins, which are subsequently degraded by the 26 S proteasome complex, is a highly regulated process leading to the modulation of transcription factor activity (13). In this report, it is shown that the ubiquitin-proteasome pathway controls the degradation of PPAR␣ protein and as such modulates the concentration of PPAR␣ in hepatocytes.…”
Section: Discussionmentioning
confidence: 77%
“…Finally, ubiquitinprotein isopeptide ligase (E3) catalyzes the covalent bond of ubiquitin to the target protein. Following this process, multiubiquitinated proteins are rapidly degraded by the 26 S proteasome (13).…”
mentioning
confidence: 99%
“…Many proteins with a structural similarity to ubiquitin present in cells, Ubls (ubiquitin-like proteins), are divided into two subclasses: small, type-1 Ubls, such as SUMO-1 and NEDD8, that are ligated to target proteins in a similar manner to ubiquitin, and type-2 Ubls containing ubiquitin-like structures within a variety of large proteins having distinct functions, such as Elongin B, Rad23, and Parkin. Although ubiquitin and type-1 Ubls are central players in post-translational protein modification, the significance of type-2 Ubls remains obscure (42,43). The lack of a diglycine motif at the C-terminal end of the ubiquitin domain suggests that Herp is a type-2 Ubl.…”
Section: Discussionmentioning
confidence: 99%
“…Ubls are conjugated to target proteins by an enzymatic cascade involving an activating enzyme (E1), a conjugating enzyme (E2), and a ligase (E3) (15)(16)(17). Ubl modification of signaling molecules and transcription factors has a large impact on gene expression (13,14).…”
mentioning
confidence: 99%